A high-resolution late Quaternary depositional history and chronology for the southern portion of the Lake Mungo lunette, semi-arid Australia. (1st April 2020) - Jankowski, Nathan R.; Stern, Nicola; Lachlan, Terry J.; Jacobs, Zenobia
Abstract: The Willandra Lakes region sits on the southern margin of Australia's arid core and is one of the oldest localities on the continent known to have been occupied by Australia's First People. The archaeological traces that accumulated in the Lake Mungo lunette paint a picture of changing land use over the past ∼50 thousand years (ka) and some of these are likely to have been responses to changes in palaeoenvironmental conditions. This study set out to determine the finest temporal resolution that can be used to study the depositional and palaeoenvironmental history of the Lake Mungo lunette. The investigation focused on the depositional history documented within stratigraphy exposed in an eroding gully in the southern part of the lunette; Gully 10. A stratigraphic framework was developed using sedimentological and soil micromorphological analysis. This framework was then fixed in time by 56 single-grain optically stimulated luminescence (OSL) age estimates. These data sets were then combined into a Bayesian model that indicated three depositional phases: >100 ka (LU1), ∼65–33 ka (LU2–LU3), and from ∼30 to 16 ka (LU4–LU9), with the late Pleistocene and Holocene samples (LU10–11) not being modelled. Furthermore, the redating of thirteen Lower and Upper Mungo OSL samples from Bowler et al. (2003)'s study of the southern tip of the lunette yielded younger age estimates for twelve of these, bringing them into line with previously published independent age control as well as the ages presented in this study. This study provides an approach for future efforts to establish consistency in age estimation and palaeoenvironmental interpretation along the length of the lunette. Highlights: 56 new single-grain OSL ages are reported for the Lake Mungo lunette. Combined OSL and soil micromorphology yields critical palaeoenvironmental detail. Redating of Bowler's transects brings chronology in line with present study. Variation exists in the deposition and preservation of sediments along the lunette.